De La Comptitivit Des Pays : Cas De laAlgrie A Travers Les IDE (Global Journal of Management and Business Research, 2014)
The competitiveness of nations has become essential for successful integration into the global economy. It is determined by the productivity with which a nation or a region uses its various resources and determining the standard of living of the nation. Algeria is carried low scores, despite the sustained economic growth,macroeconomic stability, substantial foreign exchange reserves and external debt insignificant. It gets bad ratings by independent institutions. The objective of this paper is to analyze the competitiveness of Algeria, locate its position relative to its partners, identify the real obstacles to the acquisition of competitive advantages, and propose actions to be implemented to allow the countries to become more competitive.
Keywords: competitiveness; attractiveness; economic performance; growth; innovation; algeria